Are we ready to adopt mobile money in non-profit sector? - Fakir Md Yunus; Safayet Khan; Tanjilut Tasnuba; Paroma Afsara Husain; Amanda Joy Misiti (Journal of Innovation and Entrepreneurship, 2016)
Mobile money has grown rapidly in the past few years. It has contributed to greater financial inclusion for the poor and unbanked, bringing millions of people into a formal financial system. Despite the increased use of mobile money, little research has focused on non-profits' preparedness to mobile money adoption. This article explores staff perceptions regarding mobile money at a large Bangladeshi non-profit. The objective of the study was to understand staff and clients' opinions about using mobile money specifically focusing on reliability, efficiency, and quality. In this qualitative study, we focused on five projects and conducted a total of 11 focus group discussions and 50 in-depth interviews. We found staffs and clients were amenable to using mobile money. Most people felt that using mobile money could reduce the workload, save time and money, and make life easier for both staffs and clients. However, significant client adoption barriers exist including client literacy and numeracy levels, a lack of national identity cards and challenges obtaining them, poor mobile networks in remote areas and service fees. Some staff also expressed concerns about mobile money posing a threat to their job security. If mobile money is to realize its full potential as a financial inclusion tool for the poor and unbanked, further research is needed on mobile money adoption and implementation obstacles encountered by non-profits.
Keywords: 650; Mobile money; Development programs; Non-profit sector; Bangladesh